Translating catastrophe : the aesthetics of history and modern literature - Listoe, Daniel B. (Daniel Brian) ([Place of publication not identified] : [publisher not identified], 2003)
This project explores the complex process whereby the past comes to presence. It argues that history can only emerge from the aesthetic, from judgments built upon the work of the imagination. It seeks to better understand the demands of historical reception as it studies the engagement with words from, and about, the past. The aesthetic component of history is even more pronounced, paradoxically, when there is the attempt to fathom the catastrophic, as with the Holocaust. The metaphor of translation suggests that as the past is recovered for the sake of knowledge, it is re-presented against an impossible standard of recreation. This is the ethical component of history as it brings "back" the past and speaks for the dead in an economy of recovery and loss. The difficult ethics of speaking-for is therefore at the center of this project. While inter-linguistic translation refers to the rewriting of some original text in another language, translation also represents the attempt to bring knowledge into expression. It makes the unreadable readable, even as such readability comes with a price. History is thus born as language in the necessary recreation of past events, actualities that cannot be recovered. Words, references, and presentations, in the play of past and presence, find their historical meaning through the imagination. They are, aesthetically defined, excitations that move the imagination toward understanding. This aesthetic play of the imagination and reason can be controlled in a poetics of knowledge. This study shows how the imagination's inability to apprehend the catastrophic is constitutive of history in general, which is necessarily an endless reach into the sublime. Through the literary explorations of the past, the ghostly appearance of history is also shown to be a fight for new ways of imagining the past. The role of the aesthetic in history has been long established. Only recently has it been presented as an undermining of historical authority, a hollowing that threatens the past with an unchecked relativism. Rather than flattening the hierarchy of truth-claims, however, the aesthetic of history opens the complexity of exchange between words about the past and our understandings. Through the aesthetic we can see why engagement with an original experience cannot be reduced to the empiricist formula that claims "knowing" Auschwitz is essentially the same as understanding any other moment from history. When language leads the imagination to recover what is no longer, it constructs an empiricism that makes knowledge possible. In other words, only because of its aesthetic elements can history take the place of forgetting.
Thesis (Ph. D. in English)--University of Wisconsin, Milwaukee, 2003.
Includes bibliographical references (pages 336-348).
Electronic version(s)
Photocopy.
Dissertations and Theses
Record updated by Marcive processing 21 June 2024
Keywords: History in literature; Translating and interpreting; Aesthetics in literature; Holocaust, Jewish (1939-1945), in literature